The association between patient race, treatment, and outcomes of patients undergoing contemporary percutaneous coronary intervention: Insights from the Blue Cross Blue Shield of Michigan Cardiovascular Consortium (BMC2) - Khambatta, Sherezade; Seth, Milan; Rosman, Howard S.; Share, David; Aronow, Herbert D.; Moscucci, Mauro; LaLonde, Thomas; Dixon, Simon R.; Gurm, Hitinder S. (The American heart journal, 2013)
The aim of this study was to examine if racial disparities exist in the treatment and outcomes of patients undergoing contemporary percutaneous coronary intervention (PCI). We examined the association between race, process of care, and outcomes of patients undergoing PCI between January 1, 2010, and December 31, 2011, and enrolled in the Blue Cross Blue Shield of Michigan Cardiovascular Consortium. We used propensity matching to compare the outcome of black and white patients. The study cohort comprised 65,175 patients, of whom 6,873 (10.5%) were black and 55,789 (85.6%) were white. Black patients were more likely to be younger, be female, have more comorbidities, and be uninsured. Overall, black patients were less likely to receive prasugrel (10.0% vs 14.5%, P < .001) and drug-eluting stents (62.5% vs 67.7%, P < .001), largely related to lower use of these therapies in hospitals treating a higher proportion of black patients. No differences were seen between white and black patients with regard to inhospital mortality (odds ratio 1.34, 95% CI 0.82-2.2, P = .24), contrast-induced nephropathy (OR 1.06, 95% CI 0.81-1.40, P = .67), and need for transfusion (OR 1.27, 95% CI 0.98-1.64, P = .06). White race was associated with increased odds of heart failure (OR 1.48, 95% CI 1.05-2.08, P = .024) and vascular complications (OR 1.40, 95% CI 1.03-1.90, P = .032). Compared with white patients, black patients undergoing PCI have a greater burden of comorbidities but, after adjusting for these differences, have similar inhospital survival and lower odds of vascular complications and heart failure after PCI.